1995
DOI: 10.1007/bf02178192
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent schizophrenia: A methodologic review of the current neuroimaging and neuropsychologic literature

Abstract: This paper reviews all relevant articles that reported structural neuroimaging or neuropsychological data in adolescent patients with schizophrenia. These papers were subsequently examined from a methodological perspective. Few papers have been written that have examined whether adolescent schizophrenia is associated with structural neuroimaging abnormalities or cognitive dysfunction. In these studies, major methodologic issues exist. Therefore, at present, firm conclusions cannot be made regarding the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Four independent reports find no hippocampal volume reduction in this age group. [81][82][83][84] One study has found right-sided superior temporal gyrus volume reduction, 85 while in another study this finding was absent at baseline but present at a 2-year follow-up. 86 In contrast, the thalamus appears to be reduced in volume or area in EOS.…”
Section: Adult Onset Schizophreniamentioning
confidence: 98%
“…Four independent reports find no hippocampal volume reduction in this age group. [81][82][83][84] One study has found right-sided superior temporal gyrus volume reduction, 85 while in another study this finding was absent at baseline but present at a 2-year follow-up. 86 In contrast, the thalamus appears to be reduced in volume or area in EOS.…”
Section: Adult Onset Schizophreniamentioning
confidence: 98%
“…However, many of these studies are limited by substantial methodologic flaws. In the studies that have relied on neuroimaging, flaws have included (a) limited sample sizes (Bertolino et al, 1996), (b) absence of normal control groups (Findling et al, 1995;Soares & Mann, 1997), (c) ignoring dose-related effects of concurrent medication use on structural brain changes (Soares & Mann), and (d) failing to eliminate age-related decreases in blood flow and brain structure (Schultz et al, 2002).…”
Section: Nurture: the Fundamental Significance Of Relationship As A Pmentioning
confidence: 99%
“…3 It is well known that the early stages of psychosis are accompanied by a significant cognitive impairment, but questions remain about the course of that impairment and relationships with key clinical variables. [4][5][6][7][8] The current study examines clinical status and neurocognitive functioning in a sample of adolescents with early-onset schizophrenia-spectrum disorders, and also reports on a subset that was followed longitudinally.…”
Section: Introductionmentioning
confidence: 99%